2003
DOI: 10.1046/j.1471-4159.2003.01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc inhibition of cellular energy production: implications for mitochondria and neurodegeneration

Abstract: An increasing body of evidence suggests that high intracellular free zinc promotes neuronal death by inhibiting cellular energy production. A number of targets have been postulated, including complexes of the mitochondrial electron transport chain, components of the tricarboxylic acid cycle, and enzymes of glycolysis. Consequences of cellular zinc overload may include increased cellular reactive oxygen species (ROS) production, loss of mitochondrial membrane potential, and reduced cellular ATP levels. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
225
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(237 citation statements)
references
References 56 publications
11
225
0
1
Order By: Relevance
“…5A). It has been reported that the catalytic activity of mammalian GAPDH is inhibited by a low nanomolar concentration of Zn 2ϩ (39). Consistent with this property, both Arabidopsis GAPCs were inhibited specifically by Zn 2ϩ in a dose-dependent manner, whereas Ca 2ϩ or Mg 2ϩ displayed no inhibitory effect on their catalytic activity (Fig.…”
Section: Resultssupporting
confidence: 77%
“…5A). It has been reported that the catalytic activity of mammalian GAPDH is inhibited by a low nanomolar concentration of Zn 2ϩ (39). Consistent with this property, both Arabidopsis GAPCs were inhibited specifically by Zn 2ϩ in a dose-dependent manner, whereas Ca 2ϩ or Mg 2ϩ displayed no inhibitory effect on their catalytic activity (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Our results showed that Zn-depleted cells have a lower MT expression indicating that MT is not involved in protecting against Zn deficiency-induced oxidative stress. Cells with low levels of MT are more susceptible to DNA damage and apoptotic death following exposure to stress stimuli, including oxidative stress, whereas prior induction of MT appears to offer cellular protection against oxidants (Chimienti et al 2001;Jourdan et al 2002;Dineley et al 2003;Maret et al 2002). These results suggest that DNA damaging effects of Zn deficiency may be exacerbated by lower MT concentration.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, S. pneumoniae becomes hypersensitive to oxidative stress (45,46). Zn may also bind adventitiously to other sites that do not normally contain a metal ion and thereby inhibit key enzymes in cells (35,(47)(48)(49). We have addressed this in the case of the human bacterial pathogen Streptococcus pyogenes and shown that exposure to elevated Zn results in inhibition of glycolytic enzymes and phosphoglucomutase (50).…”
Section: Antibacterial Effects Of Cu and Znmentioning
confidence: 99%